Hypothermia Improves Oral and Gastric Mucosal Microvascular Oxygenation during Hemorrhagic Shock in Dogs. (12th November 2013) - Vollmer, Christian; Schwartges, Ingo; Swertz, Meike; Beck, Christopher; Bauer, Inge; Picker, Olaf
Abstract : Hypothermia is known to improve tissue function in different organs during physiological and pathological conditions. The aim of this study was to evaluate the effects of hypothermia on oral and gastric mucosal microvascular oxygenation ( μ HbO2 ) and perfusion ( μ flow) under physiological and hemorrhagic conditions. Five dogs were repeatedly anesthetized. All animals underwent each experimental protocol (randomized cross-over design): hypothermia (34°C), hypothermia during hemorrhage, normothermia, and normothermia during hemorrhage. Microcirculatory and hemodynamic variables were recorded. Systemic (DO2 ) and oral mucosal ( μ DO2 ) oxygen delivery were calculated. Hypothermia increased oral μ HbO2 with no effect on gastric μ HbO2 . Hemorrhage reduced oral and gastric μ HbO2 during normothermia (−36 ± 4% and −27 ± 7%); however, this effect was attenuated during additional hypothermia (−15 ± 5% and −11 ± 5%). The improved μ HbO2 might be based on an attenuated reduction in μ flow during hemorrhage and additional hypothermia (−51 ± 21 aU) compared to hemorrhage and normothermia (−106 ± 19 aU). μ DO2 was accordingly attenuated under hypothermia during hemorrhage whereas DO2 did not change. Thus, in this study hypothermia alone improves oral μ HbO2 and attenuates the effects of hemorrhage on oral and gastric μ HbO2 . This effect seems to be mediated by an increased μ DO2 on the basis of increased μ flow.